Garbage Bank as an Alternative Strategy for Waste Management in Bumi Asri Housing - Sri Wulandari; Delia Ardita Pramesti; Kholilah Husni; Fauziah Ika; Ilma Rakhmadani; Muhammad Rafli Syahputra; Angga Maulana; Rizqi Junaedi Arisman; Dika Ardiansyah (Yayasan Adra Karima Hubbi, 2024)
Background. The paradigm shift of society regarding waste needs to be done sustainably. Education of awareness and skills of citizens for waste management by implementing the principles of reduce, reuse and recycle (3R) is important in solving waste problems through waste management from the source.Purpose. The paradigm shift of society regarding waste needs to be done sustainably. Method. The method used by researchers in this study is the field research method with a descriptive approach where researchers go directly to the field and see phenomena and analyze and obtain a detailed and objective picture to obtain accurate data using the Participatory Action Research (ADR) method.Results. The results of this study explain that the waste bank teaches the community to sort waste, raises public awareness to process waste wisely in order to reduce waste transported to the landfill. Conclusion. Waste banks can make residents create and shape the character of residents to be better. This can be seen from the character of residents who have knowledge in managing the environment to make it beautiful.